Hydrophobic association mediated physical hydrogels with high strength and healing ability - Geng, Yuhui; Lin, Xiao Ying; Pan, Pengju; Shan, Guorong; Bao, Yongzhong; Song, Yihu; Wu, Zi Liang; Zheng, Qiang (Polymer (Guilford), 2016)
Supramolecular polymeric hydrogels, combining the responsiveness of noncovalent interactions and good mechanical properties of polymers, have received increasing attentions due to their high strength, multi-responses to stimuli, and good processability. In this article, we develop transparent physical hydrogels by simply casting and reswelling the films of copolymers synthesized by polymerization of a hydrophilic monomer of acrylic acid (AA) with a small fraction of hydrophobic monomer of stearyl acrylate (SA). The long alkyl chains of SA units segregate in water to form hydrophobic associations, serving as the physical crosslinking junctions of gels. The gels are robust with tensile strength up to ∼2 MPa; the mechanical properties can be tuned by varying the composition of copolymers and depend on the deformation rate. The gels are responsive to temperature, pH, and ethanol solvent, which mediate the stability of the hydrophobic associations and even lead to gel-to-sol transition. Based on this reversible transition, the gels show stimuli-mediated healing ability. Gels with complex structures can be constructed by localized welding. In addition, the gels exhibit shape memory behaviour; the shape can be memorized by forming strong coordination between carboxylic acid groups and additional Fe3+ ions and relaxed by reduction of the Fe3+ ions. These gels with versatile properties should find applications such as in responsive coatings, tissue engineering, and soft actuators. [Display omitted] •Robust hydrogels with crystalline domains as physical crosslinks are facilely prepared.•The gels are velocity toughening; modulus and extensibility increase with stretch rate.•The gels are responsive to multi-stimuli, which mediate the stability of crystalline domains.•The physical gels show stimuli-triggered healing ability and shape memory behaviour.